Pemberdayaan Masyarakat Pesisir Melalui Pemanfaatan Limbah Cangkang Telur Sebagai Pupuk Organik di Desa Bumbulan, Kecamatan Paguat, Kabupaten Pohuwato - Risna Podungge; Gamar Abdullah; Sulasikin Sahdi Kadir; Citron Payu; Idawati Supu (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2024)
Empowering coastal communities through the use of eggshell waste as organic fertiliser is the development and application of innovations and technologies that are directly useful to the community to improve the quality of life and community independence. The features of the use of eggshell waste as organic fertiliser include producing new environmentally friendly natural composite materials and supporting the idea of utilising eggshell waste into products that have high economic and technological value. The business of using eggshell waste as raw material for making organic fertiliser changes the form of the primary product into a new product. The purpose of this activity is that it is hoped that the community, especially those who work as farmers, can make organic fertiliser independently whose use is more economical and environmentally friendly.